The uncarboxylated form of osteocalcin is associated with improved glucose tolerance and enhanced β-cell function in middle-aged male subjects - Hwang, You-Cheol; Jeong, In-Kyung; Ahn, Kyu Jeung; Chung, Ho Yeon (Diabetes/metabolism research and reviews, 2009)
Background Recent human studies support the notion that serum osteocalcin increases β‐cell proliferation and insulin secretion, and improves insulin sensitivity. However, no study has examined the effects of serum osteocalcin γ‐carboxylation status on these associations or determined the role of uncarboxylated osteocalcin in glucose metabolism in humans. Methods The aim of this study was to determine the association between uncarboxylated osteocalcin and β‐cell function and insulin sensitivity in humans. As many as 199 men, aged 25–60 years (mean age, 47 years), who had never been treated with glucose lowering agents, were enrolled in this cross‐sectional study. OGTT was performed and other metabolic parameters, such as, BMI, BP, lipid profiles, and both uncarboxylated and carboxylated osteocalcin plasma levels were measured. Results When subjects were divided into tertiles by uncarboxylated and carboxylated osteocalcin plasma concentrations, subjects in the upper tertile of each showed lower fasting and post‐challenge glucose levels after adjusting for age and BMI (P < 0.05). The upper uncarboxylated osteocalcin tertile was associated with higher HOMA‐B% levels, which are representative of β‐cell function (P < 0.05), and the upper carboxylated osteocalcin tertile was associated with lower HOMA‐IR values, which are representative of insulin resistance (P < 0.05). Conclusions Elevated levels of both carboxylated and uncarboxylated forms of osteocalcin were associated with improved glucose tolerance. Moreover, the uncarboxylated form of osteocalcin was found to be associated with enhanced β‐cell function, and the carboxylated form was associated with improved insulin sensitivity in middle‐aged male subjects. Copyright © 2009 John Wiley & Sons, Ltd.